Identity Crisis in Inaam Kachachi’s The American Granddaughter - Ahmed , Shawnm Marif (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The American Granddaughter is a novel written by the Iraqi writer Inaam Kachachi, and it was published in 2010. The novel has strong and impressive language as the prose of narration and stylistic elements of form; this made it possible to be familiarized through the English-speaking world as an appealing and moving story of an individual who suffered from the atrocities of war and confusion of her own identity. The story depicts the experience of Iraqi-born Zeina who lived as "second generation" immigrant and decided to visit her own country with the U.S military forces as interpreter. In Iraq, she meets her own grandmother and other relatives and begins to ask about the identity of herself and the consequences of war and human conflicts from the social and political points of view. The approaches that are used in the study and analysis of the novel include historical, sociological and psychological criticism along with some analytic remarks which are to be found in psychoanalytic and gender-based theories and criticism. The text gives the possibility of several readings in accordance with these methodologies due to its contextual element of socio-historical and psychological characteristics. ‌ This study aims at analyzing different aspects in the life of novel’s main character relatable to her conflicts between immigration and returning, her struggle with both diasporic and national origins and identities at same times, her nostalgia hence being proud of her guest country, and how she perceives herself as different from experience of her parents as immigrant.